Drying kinetics of coal under microwave irradiation based on a coupled electromagnetic, heat transfer and multiphase porous media model. (15th November 2019) - Li, He; Zheng, Chunshan; Lu, Jiexin; Tian, Li; Lu, Yi; Ye, Qing; Luo, Wenke; Zhu, Xiangnan
Highlights: Coupled electromagnetic, heat transfer and multiphase porous media model was built. Temperature rise of coal heated by microwave is characterized by "fast-slow-fast". The saturation time of the water always lags behind that of the vapour. The higher the microwave power, the quicker the fluid reaches the ultimate value. Abstract: Microwave has gained widespread popularity in coal drying. In the current electromagnetic models, coal is always assumed as a solid continuum. The thermodynamic evolution and the fluid migration in coal cannot be accurately predicted. In this study, a fully coupled electromagnetic, heat transfer and multiphase porous media model was developed to investigate the drying kinetics of coal under microwave irradiation. Results show that the temperature rise of coal during microwave irradiation is characterized by "fast-slow-fast", and water evaporation is the key factor in thermal distribution. The water in the hot spot decreases, while the vapour increases and migrates towards the cold spot. The saturation time of the water always lags behind that of the vapour. In addition, the higher the microwave power, the quicker the fluid reaches the ultimate value. The nonuniform microwave heating enhances the thermal gradient and gas pressure gradient in coal, leading to irreversible damage. Outcomes of this study can be used to identify the drying behaviors of coal during microwave irradiation and thereby help to optimize the microwave applicators.